Mangá em Cuiabá : processo de mundialização e consumo - Ueta, Taís Marie (2013)
This work analyzes the process of mundialization and consumption of manga (Japanese comics) as seen from its process of actualization in the city of Cuiabá, Mato Grosso State, Brazil – based on these main concepts: late capitalism, as defined by Ernest Mandel (1982); the hybridity and consumption as a category for thought, by Néstor García Canclini (2003; 2008); the mundialization, proposed by Renato Ortiz (1994; 2000) and media convergence, as thought by Henry Jenkins (2009). The trajectory of manga is shown as being a mediatic product, from stories in scrolls of 12th Century to the usage of modern Western techniques of editing. The complexity attributed to Japanese writing favors the prevailing of a image-based communication, alongside with adoption of another aesthetical ways such as the language of the cinema. The configuration of manga as a global product has occurred due to its aesthetical distinction, with the narratives which bring up human dramas, hypothetically universal, and alongside a convergence process which is unique to Japan. It also contains the ways manga has traced in Brazil, through Japanese immigrants. The scene within Cuiabá, on the other hand, is narrated through its spaces – physical (newspaper stands, second-hand shops, specialized shops and the Japanese Language School) and temporal (events). The characters of this scene (64 respondents of the questionnaire) help to contextualize and actualize (Pierre Lévy) the mundialization process, seen from the perspective of Cuiabá, Mato Grosso State’s capital city